2014
DOI: 10.5194/tc-8-959-2014
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory subglacial drainage in the absence of surface melt

Abstract: Abstract. The presence of strong diurnal cycling in basal water pressure records obtained during the melt season is well established for many glaciers. The behaviour of the drainage system outside the melt season is less well understood. Here we present borehole observations from a surge-type valley glacier in the St Elias Mountains, Yukon Territory, Canada. Our data indicate the onset of strongly correlated multi-day oscillations in water pressure in multiple boreholes straddling a main drainage axis, startin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(105 citation statements)
references
References 58 publications
(77 reference statements)
9
96
0
Order By: Relevance
“…Borehole data from Schoof et al (2014) demonstrate that transient pressure oscillations occurred during the winter in a glacier in the Yukon Territory of Canada. These were driven by low water flux rates in a constricted system.…”
Section: Pressure Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Borehole data from Schoof et al (2014) demonstrate that transient pressure oscillations occurred during the winter in a glacier in the Yukon Territory of Canada. These were driven by low water flux rates in a constricted system.…”
Section: Pressure Wavesmentioning
confidence: 99%
“…The oscillations lasted over a period of days, as opposed to years as seen in our model of Antarctic ice streams. Schoof et al (2014) modeled this system on an idealized flowline and demonstrated that storage of water is an important control on the timing of internally driven oscillations. Given the significant differences between a mountain glacier and an Antarctic ice stream it is not surprising that system oscillations would occur at different periodicities.…”
Section: Pressure Wavesmentioning
confidence: 99%
“…Similar to the study by Bougamont et al (2014), modelled velocities do not capture this behaviour. These velocity events may be the result of internal dynamics of water stored over winter (Schoof et al, 2014), such as flooding events, that the subglacial hydrology model does not capture or early season melt which RACMO2.3 does not predict.…”
Section: Model Fitmentioning
confidence: 99%
“…Dampening by one order of magnitude of the anti-correlated response is observed from water pressure in boreholes in the Greenland ice sheet (Meierbachtol et al, 2013;Andrews et al, 2014) and alpine glaciers (Gordon et al, 1998;Schoof et al, 2014), although the difference in amplitude is sometimes small (Murray and Clarke, 1995;Dow et al, 2011). Capturing the spatial variation of this dampening can help to identify the origin of the anti-correlation and whether it is a response caused by ice dynamics or, as observed here, by the hydrological system.…”
Section: Discussionmentioning
confidence: 91%